Strong spin-orbit coupling and Dirac nodal lines in the three-dimensional electronic structure of metallic rutile IrO2 - Xu, X.; Jiang, J.; Shi, W. J.; Suess, Vicky; Shekhar, Chandra; Sun, S. C.; Chen, Y. J.; Mo, S-K; Felser, Claudia; Yan, B. H.; Yang, H. F.; Liu, Z. K.; et al. (Physical Review B, 2019)
Using high-resolution angle-resolved photoemission spectroscopy and ab initio calculation, we have studied the bulk and surface electronic structure of metallic rutile 5d transition metal oxide IrO2 that harbors both edge and corner sharing Ir-O octahedrons. We observe strong modulation of the band structure by spin-orbit coupling (SOC). The measured band structure is well reproduced by our ab initio calculation without band renormalization, suggesting the absence of the SOC-enhanced correlation effect in IrO2. In accordance with the calculation, we visualize two types of Dirac nodal lines (DNLs) protected by mirror symmetry and nonsymmorphic crystal symmetry, respectively. SOC gaps the first type of DNLs, which may contribute largely to the strong spin Hall effect. The second type of DNLs at the edges of Brillouin zone, however, remain intact against SOC. Our results not only provide important insights into the exotic transport properties of IrO2, but also shed light on the understanding of the role of SOC in the iridate family.
CRIS-Team Scopus Importer:2022-04-14